Integral Error Representation of Hermite Interpolating Polynomial and Related Inequalities for Quadrature Formulae. Issue 6 (1st November 2016) - Aras-Gazić, Gorana; Pečarić, Josip; Vukelić, Ana
Abstract: We consider integral error representation related to the Hermite inter-polating polynomial and derive some new estimations of the remainder in quadrature formulae of Hermite type, using Hölder's inequality and some inequalities for the Čebyšev functional. As a special case, generalizations for the zeros of orthogonal polynomials are considered.